An Analysis of Internet Enterprise Value Evaluation Method Based on ARIMA - Chen, Ling (Journal of physics. Conference series, 2021)
With the rapid development of the times, the Internet has been deeply integrated into various fields, and many Internet companies have emerged at the historic moment, and economic activities such as mergers, reorganizations, acquisitions, issuance and listing, equity swaps, mortgages, bankruptcy and liquidation of Internet companies have also increased frequently. This has led to more and more value evaluation activities related to Internet companies, and the business model of Internet companies is different from traditional companies, so traditional corporate value evaluation methods cannot fully meet the special requirements of Internet company value evaluation. Therefore, we need to establish a sound Internet enterprise value evaluation system, and use more scientific and reasonable evaluation methods to ensure the interests of all parties to the transaction. Starting from the operating characteristics of Internet companies, this article analyzes the characteristics and difficulties of Internet corporate value evaluation, clarifies the effectiveness and limitations of the income method in Internet enterprise value evaluation, introduces the ARIMA model to improve the traditional income method and takes NetEase as an example. This method is applied to practice to verify its feasibility. So as to provide a scientific and reliable reference basis for Internet enterprise value evaluation.